British Association of Urological Surgeons (BAUS) and Nurses (BAUN) consensus document: management of the complications of long‐term indwelling catheters. (17th May 2021) - Reid, Sheilagh; Brocksom, Jane; Hamid, Rizwan; Ali, Ased; Thiruchelvam, Nikesh; Sahai, Arun; Harding, Chris; Biers, Suzanne; Belal, Mo; Barrett, Rachel; Taylor, Julia; Parkinson, Richard
: Objective: To look at best evidence and expert opinion to provide advice in the form of a consensus statement lead by Female, Neurological and Urodynamic Urology (FNUU) section of the British Association of Urological Surgeons (BAUS) in conjunction with the British Association of Urological Nurses (BAUN). Methods: Initially a literature search was performed with incorporation of aspects of the existing guidance and further informed by UK best practice by core members of the group. The document then underwent reviews by the FNUU Executive Committee members, the BAUN executive committee, a separate experienced urologist and presented at the BAUS annual meeting 2020 to ensure wider feedback was incorporated in the document. Results: Complications of long‐term indwelling catheters include catheter‐associated urinary tract infections (CAUTI), purple urine bag syndrome, catheter blockages, bladder spasms (causing pain and urinary leakage), loss of bladder capacity, urethral erosion ("catheter hypospadias")/dilatation of bladder outlet and chronic inflammation (metaplasia and cancer risk). Conclusions: We have provided a list of recommendations and a troubleshooting table to help with the management of the complications of long term catheters.